Loser Geopositioning - No Payoff For Galileo Navigation System. - Sweet, W. (IEEE spectrum)
The idea of a European geopositioning system similar to the U.S. Global Positioning System originated a decade ago. Today the system is five years behind schedule and, in terms of public funding, at least a couple of billion euros over budget.